A Case–Control Study of ADCY9 Gene Polymorphisms and the Risk of Hepatocellular Carcinoma in the Chinese Han Population - Chao, Xu; Jia, Yong; Feng, Xuesong; Wang, Guoquan; Wang, Xiaoping; Shi, Hailong; Zhao, Fei; Jiang, Chao (Frontiers in Oncology, 2020)
Background: Adenylyl cyclase type 9 (ADCY9) modulates signal transduction by producing the second messenger cyclic AMP. It has been reported that ADCY9 gene polymorphisms were associated with cancer development. The aim of this study was to investigate whether ADCY9 gene polymorphisms could contribute to the susceptibility of hepatocellular carcinoma (HCC) in the Chinese Han population. Methods: In the present study, five single-nucleotide polymorphisms (SNPs) in ADCY9 were genotyped using Agena MassARRAY platform in 876 subjects from China. Logistic regression was used to assess the effects of SNPs on HCC risk. Associations were also evaluated for HCC risk stratified by age and gender. False discovery rate (FDR) was used to correct multiple testing. Results: After adjusting for age and gender, we found a significant relationship between heterozygous genotypes of rs2531995 and HCC risk (OR = 1.34, 95% CI = 1.01–1.77, p = 0.045). ADCY9 rs2230742 had a strong relationship with lower risk of HCC in allele (p = 0.006), co-dominant (p = 0.023), dominant (p = 0.010), and additive (p = 0.006) models. Stratified analysis showed that rs879620 increased HCC risk and rs2230742 was associated with lower risk of HCC in the individuals aged 55 or younger, rs2531992 significantly decreased HCC risk in the elder group (age > 55). For women, rs2230742 and rs2230741 were significantly associated with HCC risk in multiple models (p < 0.05). FDR analysis showed that rs2230742 could protect individuals from HCC risk in the allele model (FDR-p = 0.030). In addition, haplotype analysis indicated that Crs879620Ars2230742Ars2230741 haplotype was a protective factor for HCC (OR = 0.67, 95% CI = 0.50–0.89, p = 0.007, FDR-p = 0.028). Conclusion: Our findings suggest that ADCY9 gene polymorphisms are associated with HCC risk in the Chinese Han population.